1988
DOI: 10.1079/bjn19880028
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid and cholesterol excretion in human beings given soya-bean-and meat-protein-based diets: a study in ileostomy subjects

Abstract: 1. The effect of partial replacement of meat protein with three different soya-bean-protein products on bile acid and cholesterol excretion was studied in seven ileostomy subjects. Four different test diets containing 60 g meat, rice and bread protein, or a replacement of 250 g protein/kg total dietary protein by soya-bean protein from soyabean flour, soya-bean concentrate or soya-bean isolate, were randomly assigned to the subjects in 2-d periods.2. Ileostomy contents were collected at 2-h intervals during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Higaki et al [87] reported that a soybean protein resistant to digestion captures bile acids and stimulates faecal bile acid excretion applying in vitro testing and a rat model. On the other hand, Bosaeus et al [88] investigated soy bean proteins as alternatives to meat proteins and did not find significant influences on ileostomy bile acid concentrations. A recent study of Wang and Fan [89] focused on structural characteristics of the interaction between zein, a plant protein isolated from maize, and sodium taurocholate.…”
Section: Interactions Between Bile Acids and Proteinsmentioning
confidence: 98%
“…Higaki et al [87] reported that a soybean protein resistant to digestion captures bile acids and stimulates faecal bile acid excretion applying in vitro testing and a rat model. On the other hand, Bosaeus et al [88] investigated soy bean proteins as alternatives to meat proteins and did not find significant influences on ileostomy bile acid concentrations. A recent study of Wang and Fan [89] focused on structural characteristics of the interaction between zein, a plant protein isolated from maize, and sodium taurocholate.…”
Section: Interactions Between Bile Acids and Proteinsmentioning
confidence: 98%